Architectures of the soul: Multidisciplinary approaches to the experiences and landscapes of seclusion and solitude - Volzone, R.; Fontes, J. L.; Martins, D. (2022)
This book aims to promote discussion around the architecture and landscapes associated with spiritual practices tied to solitude and seclusion, in their various forms – both within given spiritual and religious traditions, and in more secularized forms – and the ways in which such practices relate to, transform, or create a particular landscape. The book is organised around four themes underlying the two seminars, including 22 texts and 37 authors, transdisciplinary and transnational contributions, taking a diachronic perspective.